STEROIDAL SAPOGENINS 166 THE NEOSAPOGENINS - MARKER, RE; LOPEZ, J (BOTANICA-MEX S. A, TEXCOCO, EM, MEX, 1947)
A correlation has been made between all of the known steroidal sapogenins with the neo side chain.
J OPT SOC AM
Keywords: STEROIDAL SAPOGENINS. 166., NEOSAPOGENINS; QUIMICA; QUIMICA INORGANICA; QUIMICA DE LOS PIGMENTOS